PENGARUH KOMPETENSI, MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI (Studi Pada Dinas Perhubungan Kota Semarang) - Leni Fitri Astuti, 15.05.51.0129; Murdiyanto, Agus (Students' Journal of Economic and Management, 2019)
This study aims to analyze the effect of Competence, Motivation and Organizational Culture on Employee Performance at the Semarang City Transportation Agency. This research was conducted using primary data, namely data obtained directly from the source. The population of this study was 60. Data collection techniques were carried out by questionnaire. Before carrying out the analysis, validation and reliability tests were carried out on the questionnaire. Next, the hypothesis test was carried out with the help of SPSS version 20. Based on the regression test conducted it was found that competence, motivation, organizational culture had a positive and significant effect on employee performance. R square value 79.9%. This means that 79.9% of the Y variable can be explained by the independent variable and the remainder is explained by other variables outside the model.